Recovery of Cenobiont Populations of Bifidobacterium spp. and Lactobacillus spp. After Treatment of Experimental Dysbiosis With Immobilized Probiotic Escherichia coli M-17 Stored at Low Temperatures - Petrov , Illia; Ananina , Ganna (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 293